Current Risk Management Strategies for the Mining Industry in Gorontalo: A Review - Habie, Riska (Eastasouth Institute, 2025)
This research analyzes current risk management strategies relevant to the mining industry in Gorontalo, with a focus on mitigating negative impacts on the environment and local communities. Through a qualitative approach that includes a literature review and objective situation analysis of the assisted communities, this study aims to identify best practices in effective risk management. The research results highlight the importance of integrating cutting-edge technology, such as data analysis and the Internet of Things (IoT), in improving safety and cleanliness in the workplace (K3). Apart from that, continuous training for employees is also considered a crucial step in increasing awareness and responsibility for K3. The importance of a deep understanding of geotechnical conditions was also emphasized, especially in dealing with potential risks such as landslides. Strong partnerships between companies, governments and local communities are also considered important in managing environmental risks effectively. By adopting a sustainable approach that focuses on technology, training and partnerships, the mining industry in Gorontalo can maintain a balance between economic growth and environmental conservation. In conclusion, an integrated and proactive risk management strategy is needed to ensure the sustainability of the mining industry while still paying attention to the resulting social and environmental impacts.